Painless Silent Chronic Fibrosing Pancreatitis Caused Complete Biliary Obstruction in a Toddler: A Case Report - Magd Ahmed Kotb; Mohamed Elbarbary; Sherif Kaddah; Martina Magdy; Rania Hamdy; Reham Osama Mahmoud; Nevian Nabil; Noha Adel Yassin; Ahmed Nabil; Ahmed El Hatw; Sayed Khedr (Pediatric Sciences Journal)
Chronic pancreatitis in toddlers presents typically by epigastric pain with radiation to the back, steatorrhea, or chronic weight loss despite adequate nutrition, nausea, vomiting, and/or diarrhea. Among adult almost 10% with chronic pancreatitis do not report pain. We report a 21-month-old boy who presented by jaundice, clay colored stool, elevated liver enzymes, and hepatomegaly. The mother reported that the child had no complaints otherwise. Hepatitis A virus IgM was positive. He was advised conservative treatment with no response. Two months later he presented by olive green jaundice, pruritus, clay stools, and no other complaints. The coronavirus disease-2019 (COVID-19) anti-spike IgM was positive. Abdominal ultrasound revealed dilatation of intrahepatic biliary radicals, right, left and common hepatic ducts with no abrupt dilation at common bile duct. MRCP and dynamic MRI of pancreas confirmed the findings and detected a bulky head of pancreas with atrophic body and tail compressing the common bile duct. He underwent percutaneous trans hepatic drainage (PTD) with T tube insertion for drainage of the biliary obstruction followed by Frey procedure with coring of pancreatic head to allow biliary drainage. The post-operative course was uneventful and within 3 weeks the jaundice cleared completely. The amylase and lipase dropped after 8 weeks. Chronic fibrosing pancreatitis might be associated with acute hepatitis or COVID-19 and might be painless and get masked by the obstructive jaundice. Chronic pancreatitis presenting by biliary obstruction might be mistaken for prolonged cholestatic hepatitis A infection. Chronic pancreatitis should be excluded in children with suspected prolonged cholestasis. Percutaneous trans hepatic drainage was a necessary step before Frey’s procedure. Chronic pancreatitis in children is amenable to successful surgical intervention.